A Supplier Strategy to Control the Bullwhip Effect - El-Tannir, Akram Amine (ExcelingTech, 2019)
Strategies to control the Bullwhip effect in supply chains have been the focus of a substantial amount of research in the last few decades. Some strategies were based on the implementation of information sharing and collaboration with retailers. Other strategies suggested the use of the vendor-managed inventory (VMI) approach. VMI however, requires significant implementation challenges to gain the trust and acceptance of the retailers as it gives the full control of the retailers inventory to the supplier. New type of strategies has been recently suggested where the supplier can control retailers orders with replenishment decisions that can decrease the effect of the bullwhip phenomenon by controlling the replenishment orders to a pool of retailers and ended up with preference discrimination among the retailers. This paper proposes a strategy that controls the fulfillment quantities to individual retailers orders, independently of other retailers, in a way that conserves the expected mean of these orders while reducing their variance. This will lead to reducing the impact of the bullwhip effect on the supplier side. Fortunately, this proposed strategy eventually improves the service level on the retailer side.